Madkhali’s criticism of Sayyid Quṭb: a critique of the critique - Arikewuyo, Nafiu Ahmed (IJISH (International Journal of Islamic Studies and Humanities), 2023)
From the 60s of the 20th century, the works of Sayyid Quṭb have enormous influence on the thought of Muslim youths and Islamists. The core message of his works is establishing the supremacy of Islamic law in all facets of life and outright condemnation of the subsisting order of the day concerning the political and socio-economic operations in Muslim nations. The effect of his thoughts on Muslim youths is visible in the resurrection of Islamists who have become a thorn in the flesh of political dictators and autocratic monarchs in Arabia. As part of efforts to neutralize the effects of Quṭb’s works on the ever-increasing Muslim youths in Saudi particularly and the Muslim world at large, Rabi’u Madkhali, a senior Salafi diehard with much influence in Madinah, kickstarted the project of refuting what he termed as "theological deviations” and “rebellious approach” in Quṭb’s thoughts. His works have given birth to a large number of Muslim youths who dedicate an extraordinary commitment to pathological hatred for Quṭb, his works, associates, and students. This article aims to criticize some submissions of Madkhali on Quṭb’s thought. The article which is library-based adopts an analytical method of research. Two issues, which include law enactment in a Muslim state and the abolition of the slavery system, are selected. The paper found that Madkhali’s refutations are highly characterized by accusations that need unequivocal proof, misinterpretation of Quṭb’s statements, and emotional submissions. It recommends further investigation into other Madkhali’s refutation of Sayyid Quṭb.